Characterization of an entomopathogenic fungi target integument protein, Bombyx mori single domain von Willebrand factor type C, in the silkworm, Bombyx mori. Issue 3 (7th February 2017) - Han, F.; Lu, A.; Yuan, Y.; Huang, W.; Beerntsen, B. T.; Huang, J.; Ling, E.
Abstract: The insect cuticle works as the first line of defence to protect insects from pathogenic infections and water evaporation. However, the old cuticle must be shed in order to enter the next developmental stage. During each ecdysis, moulting fluids are produced and secreted into the area among the old and new cuticles. In a previous study, the protein Bombyx mori single domain von Willebrand factor type C (BmSVWC; BGIBMGA011399) was identified in the moulting fluids of Bo. mori and demonstrated to regulate ecdysis. In this study we show that in Bo. mori larvae, BmSVWC primarily locates to the integument (epidermal cells and cuticle), wing discs and head. During the moulting stage, BmSVWC is released into the moulting fluids, and is then produced again by epidermal cells after ecdysis. Fungal infection was shown to decrease the amount of BmSVWC in the cuticle, which indicates that BmSVWC is a target protein of entomopathogenic fungi. Thus, BmSVWC is mainly involved in maintaining the integrity of the integument structure, which serves to protect insects from physical damage and pathogenic infection.